A polymorphism in the 5'-flanking region of the melanocortin-4 receptor gene is associated with carcass traits in quails - FU, J; NING, F Y; DU, Z H; YANG, C S; YANG, H Y; BAI, X J (The Indian Journal of Animal Sciences, 2012)
ABSTRACT The melanocortin-4 receptor gene (MC4R) has been implicated in regulation of feeding behavior and body weight. Its gene sequence and protein function exhibits high evolutionary conservation and have been studied extensively in humans, mice, pigs and chickens. Quail MC4R is nearly identical to chicken MC4R, but little is known about its function. Thus, we investigated whether polymorphisms in the MC4R 5’-flanking region were associated with quail carcass traits. Chinese recessive white feather layer quails (n,233) and French Shaweimate meat-type quails (n,307) were assessed for body weight and carcass traits for use in statistical correlation analysis with genomic sequence data. Only one SNP was detected in the MC4R 5′-flanking regions of each quail type: 407A>G in laying quails and 543A>G in meat-type quails. The mutation in laying quails produced three genotypes: AA, BB, and AB; the A and B allele frequency was 0.416 and 0.584, respectively. Statistical analysis of variance revealed that MC4R polymorphism was associated with breast muscle weight (BMW), leg muscle weight (LMW) and heart weight in laying quails.The mutation in meat-type quails produced three genotypes as well: CC, DD, and CD; the C and D allele frequency was 0.495 and 0.505, respectively. Statistical analysis of variance revealed that the MC4R polymorphism was associated with body weight, carcass weight, semi-eviscerated weight, eviscerated weight and heart weight in meat-type quails. Our findings suggest that the MC4R gene could be a qualitative trait locus or linked to a major gene that affects carcass traits in quails.